The Linguistic Mechanisms of Trauma Discourse - Matei, Mădălina (Elsevier Ltd.., 2013)
Trauma discourse is the instance in which linguistic mechanisms reveal the speaker's evaluation of their traumatic experience. Language can also vary according to the distance of the subject in relation to the traumatic event. The aim of this study is to detect the discursive mechanisms that speakers use when narrating traumatic events and to discover the roles that certain language items might have in the construction of trauma discourse. For this purpose, interviews in which speakers recount traumatic experiences, such as political persecution or deportation, are studied in order to single out the discursive patterns that emerge within trauma discourse.
Keywords: trauma discourse; narrative; silence; collective trauma; discourse markers